2022
DOI: 10.48550/arxiv.2205.12290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From locality to irregularity: Introducing local quenches in massive scalar field theory

Abstract: In this paper, we initiate the study of the local quenches in non-conformal field theories. In particular, we consider the dynamics of excited local states in massive scalar field theory in an arbitrary spacetime dimension and generalize the well-known two-dimensional CFT results. We derive the energy density, U (1)-charge density and φ 2 (x)-condensate post-quench dynamics and identify different regimes of their evolution depending on the values of the field mass and the quench regularization parameter. For m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Besides the T T deformation, studying the free field theory with mass deformation is also interesting. In [30], authors showed the entanglement entropy of free fermions and scalars [51] with mass deformation matches the results from the holographic calculation, which suggests that the free field theory is useful for understanding the holography. Further, one can obtain the modular Hamiltonian and its flow by turning on an local operator in the path integral formalism in [32,55], as well as the time evolution of entanglement entropy for free fermion under the local bilinear operator deformation [60].…”
Section: Jhep09(2022)247mentioning
confidence: 65%
“…Besides the T T deformation, studying the free field theory with mass deformation is also interesting. In [30], authors showed the entanglement entropy of free fermions and scalars [51] with mass deformation matches the results from the holographic calculation, which suggests that the free field theory is useful for understanding the holography. Further, one can obtain the modular Hamiltonian and its flow by turning on an local operator in the path integral formalism in [32,55], as well as the time evolution of entanglement entropy for free fermion under the local bilinear operator deformation [60].…”
Section: Jhep09(2022)247mentioning
confidence: 65%
“…in non-conformal field theories [9]. In CFT's that admit a gravity dual, such quenches are dual to an in-falling particle in the bulk.…”
Section: Jhep04(2023)028mentioning
confidence: 99%
“…Their holographic dual involves a dynamical geometry that can be obtained from the back-reaction of a massive particle (or generally a bulk field), which is dual to that local operator [19]. In particular, entanglement evolution in these states has been studied extensively in the context of quantum quenches [20][21][22][23][24][25][26][27], scrambling [28,29], quantum chaos [30][31][32][33] as well as bulk reconstruction in AdS/CFT [34][35][36]. Certainly, this family provides very important and analytically tractable data points in the "spacetime from entanglement" program.…”
Section: Introductionmentioning
confidence: 99%